2003
DOI: 10.1539/joh.45.335
|View full text |Cite
|
Sign up to set email alerts
|

The New BMI Criteria for Asians by the Regional Office for the Western Pacific Region of WHO are Suitable for Screening of Overweight to Prevent Metabolic Syndrome in Elder Japanese Workers

Abstract: (WHO, 1998). It was suggested that Japanese, categorized as having normal weight (BMI of less than 25.0), as defined by the WHO (2000), have an increasing tendency toward metabolic syndrome. Our objective was to analyze metabolic syndrome in "Overweight" with BMI of 23.0-24.9 in Japanese workers, and to assess the suitability for Asians of the Regional Office for the Western Pacific Region of WHO criteria pertaining to obesity (WPRO criteria, 2000). We conducted a cross-sectional study in the workplace settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
265
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(290 citation statements)
references
References 27 publications
6
265
2
4
Order By: Relevance
“…A response of 1 for a question was considered the least functional and a response of 5 the most functional. The severity of ED was classified into the following five grades based on the six-item EF domain: severe (6-10); moderate (11)(12)(13)(14)(15)(16); mild to moderate (17-21); mild (22)(23)(24)(25); or no ED (26-30).…”
Section: Methodsmentioning
confidence: 99%
“…A response of 1 for a question was considered the least functional and a response of 5 the most functional. The severity of ED was classified into the following five grades based on the six-item EF domain: severe (6-10); moderate (11)(12)(13)(14)(15)(16); mild to moderate (17-21); mild (22)(23)(24)(25); or no ED (26-30).…”
Section: Methodsmentioning
confidence: 99%
“…It is calculated on the basis of weight in kg divided by the square of height in meters, (kg/m 2 ). A person is considered to be obese if its BMI is greater than or equal to 25 (Anuurad et al, 2003). Although the findings on obesity are mixed, but recent studies suggest that obesity is consistently related to aggressive prostate cancer (Hsing et al, 2000).…”
Section: Obesitymentioning
confidence: 99%
“…3,4 A study from Korea showed the lowest mortality in the BMI range 23-24.9, 5 which is actually classified as overweight according to WHO suggestions as regarding subjects in East and Southeast Asia. 6 In an earlier Swedish study no excess mortality was found in subjects with overweight. 7 Thus, in general the lowest overall mortality seems to be found in the BMI interval between 20 and 30, that is, classified as normal or overweight.…”
Section: Introductionmentioning
confidence: 86%